Model Integratif Storytelling Berbasis Kearifan Lokal Dan Media Interaktif Dalam Penguatan Pendidikan Karakter Anak Usia Dini - Fatmawati, Fitria Desiana; Faizi, Achmad; Hardinanto, Eko (Jurnal Ragam Pengabdian, 2026)
Character education in early childhood requires a learning strategy capable of instilling values ​​in a meaningful and sustainable manner. This study aims to analyze the effectiveness of storytelling methods in instilling character values ​​in early childhood and examine the strengthening of its implementation through the integration of media and learning contexts. The study used a qualitative approach with a descriptive design and was conducted at Raudhatul Athfal Al Khotib with fifteen children aged five to six years as subjects. Data were collected through observation, interviews, and documentation over a three-month period. The results showed that storytelling methods were able to increase children's empathy and cooperation behavior, demonstrated through sharing, helping friends, and active involvement in group activities. However, some children were still inconsistent in applying character values ​​in real situations, so that internalization of values ​​was not optimal. The research findings also showed that the effectiveness of storytelling methods increased when combined with interactive visual media, local wisdom content, and reflection activities that encourage a deeper understanding of values. The novelty of this study lies in the development of an integrative model that combines narrative, interactive media, cultural context, and reflection as a strategy to strengthen character education. Thus, storytelling methods function not only as a means of conveying stories, but also as a comprehensive strategy to develop early childhood character more effectively and sustainably.